Implementation of the Cooperative Integrated Reading and Composition (CIRC) model on students’ understanding in solving mathematical story problems (BIS Humanities and Social Science, 2026)
This study aims to determine the state of mathematics learning at MI Muhammadiyah Blondo prior to the implementation of the CIRC model, understand the steps for applying the CIRC model during the classroom learning process, and determine the effect of the CIRC model on students’ understanding in solving mathematical word problems. This research used quantitative study utilizing a pre-experimental method with a one-group pre-test post-test design. The subject of this research was madrasa ibtidaiyah Blondo with 20 students used fractions as the research material. The CIRC model was applied in groups of 4-5 students, where the researcher used a purposive sampling technique for group division to ensure equal distribution and heterogeneity among group members. The results showed that the average student pre-test score before the implementation of the CIRC model was 64.5. However, after the implementation of the CIRC model, the average student post-test score was 83. Based on the normality test results, the pre-test significance value was 0.200 and the post-test significance value was 0.061, both greater than 0.05, indicating that the data is normally distributed. The T-test results from the students’ pre-test and post-test scores obtained a t-count value of 7.594. When comparing the t-table and t-count values, the t-count 7.594 was greater than the t-table 2.093, therefore H0 is rejected and Ha is accepted. Thus, it can be concluded that the CIRC model influences students’ understanding in solving mathematical word problems.